Cardioprotective effects of Schisantherin A against isoproterenol-induced acute myocardial infarction through amelioration of oxidative stress and inflammation via modulation of PI3K-AKT/Nrf2/ARE and TLR4/MAPK/NF-κB pathways in rats - Xiaolong Mi; Zhijun Zhang; Jinfang Cheng; Zheng Xu; Kaiyi Zhu; Yunxia Ren (BMC, 2023)
Abstract Background and aims The scientific community is concerned about cardiovascular disease mortality and morbidity, especially myocardial infarction (MI). Schisantherin A (SCA), a dibenzocyclooctadiene lignan monomer found in S. chinensis fruits has cardiovascular advantages such as increasing NO production in isolated rat thoracic aorta and reducing heart damage caused by ischemia-reperfusion (I/R) through decreasing apoptosis. The present study was undertaken to explore the potential effects of SCA on ISO-induced myocardial infarction in rats. Methods Rats were randomly allocated to four groups: control; ISO-treated, and two additional groups of ISO + SCA (5 or 10 mg/kg body weight). All SCA-treated groups were administered with SCA for 20 days and all ISO groups were challenged with ISO on days 19 and 20. Results SCA significantly attenuated ISO-induced rise in heart/body weight ratio, myocardial infarct size, and cardiac functional biomarkers (CK-MB, cTnI and BNP). SCA pre- and co-treatment resulted in a significant reduction in oxidative stress (via MDA, NO and GSH and increased activities of SOD, CAT and GPx) and inflammation (via decreased levels of TNF-α, IL-6 and IL-1β) markers when compared to the same levels in cardiac tissue of ISO-treated rats. This study also showed that SCA protects ISO-induced oxidative stress and inflammation by activating the PI3K-AKT/Nrf2/ARE pathway and suppressing TLR4/MAPK/NF-κB pathways. Furthermore, SCA treatment protected histopathological alterations observed in only ISO-treated cardiac transverse sections of rats. Conclusion In conclusion, the findings of this study suggest that SCA protects against cardiac injury in the ISO-induced MI model of rats.